2004
DOI: 10.1046/j.1365-2702.2003.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental elements affecting the decision‐making process in nursing practice

Abstract: Interpersonal and technological interruptions were features highlighted in the study, features which could jeopardize the decision-making outcome. Therefore, it is of greatest importance that nurses learn to use decision-making strategies to guarantee patient care security and patient care quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 27 publications
5
79
1
4
Order By: Relevance
“…7,8,[12][13][14][15][16] Other avoidable interruptions cited in the literature are the tendency of nurses to interrupt each other with conversations unrelated to medication administration 7,[17][18][19] while preparing medications and to respond immediately to requests from others when interrupted. 7,15,20 These findings support the idea that interruptions are an accepted part of nursing practice and suggest the Attendance at the National Teaching Institute was the inspiration for this project and the springboard for addressing existing nursing concerns about interruptions. need for culture change to limit avoidable interruptions, especially during complex or high-risk activities such as medication administration.…”
Section: Review Of the Literaturesupporting
confidence: 65%
“…7,8,[12][13][14][15][16] Other avoidable interruptions cited in the literature are the tendency of nurses to interrupt each other with conversations unrelated to medication administration 7,[17][18][19] while preparing medications and to respond immediately to requests from others when interrupted. 7,15,20 These findings support the idea that interruptions are an accepted part of nursing practice and suggest the Attendance at the National Teaching Institute was the inspiration for this project and the springboard for addressing existing nursing concerns about interruptions. need for culture change to limit avoidable interruptions, especially during complex or high-risk activities such as medication administration.…”
Section: Review Of the Literaturesupporting
confidence: 65%
“…Thus, one might question whether employers look for both competence and an ability to adapt to one's work environment when hiring nurses. The findings of this study indicate that nurses try to avoid conflicts (Duddle and Boughton 2007) and follow the desires of co-workers (Hedberg and Sätterlund Larsson 2004). Yet the nurses interviewed here seem to adapt to various working conditions while remaining conscious of when they need to learn and how they learn from others.…”
Section: Nurses Work As a Learning Environmentmentioning
confidence: 73%
“…Within the hospital environment, autonomy and control over nursing care delivery have positive influences on nurses' interprofessional relationships (Budge et al 2003). Nevertheless, nurses show consideration for other members of the work community as they try to avoid conflicts (Duddle and Boughton 2007) and interrupt their activities to address the desires from other team members (Hedberg and Sätterlund Larsson 2004). Hence, a social environment should not only provide opportunities to learn, but should also enable nurses to engage in complex activities and relationships in their work.…”
Section: Introductionmentioning
confidence: 99%
“…When their children's care management problems came into question, mothers interrupted the medication preparation and administration processes of nurses. While patient-caused interruption was placed on the top in the study of Palese et al (4), it was reported to cause interruptions by 24.7% in the study of Hedberg and Larsson (17). These interruptions were unpredictable and unanticipated.…”
Section: Discussionmentioning
confidence: 99%